Looking for the elusive lung stem cell niche - Banerjee, Ena Ray (Transl Respir Med, 2014)
This discourse contains three perspectives on various aspects of Stem Cell Biology and tools available to study and translate into Regenerative Medicine. The lung incessantly faces onslaught of the environment, constantly undergoes oxidative stress, and is an important organ of detoxification. In degenerative diseases and inflammation, the lung undergoes irreversible remodeling that is difficult to therapeutically address and/or transplant a dying tissue. The other difficulty is to study its development and regenerative aspects to best address the aforementioned problems. This perspective therefore addresses- firstly, review of types of stem cells, their pathway of action and models in invertebrate organisms vis-a-vis microenvironment and its dynamics; secondly, stem cells in higher organisms and niche; and lastly data and inference on a novel approach to study stem cell destruction patterns in an injury model and information on putative lung stem cell niche. Stem cells are cryptic cells known to retain certain primitive characteristics making them akin to ancient cells of invertebrates, developmental stages in invertebrates and vertebrates and pliant cells of complex creatures like mammals that demonstrate stimulus-specific behavious, whether to clonally propagate or to remain well protected and hidden within specialized niches, or mobilize and differentiate into mature functionally operative cells to house-keep, repair injury or make new tissues. In lung fibrosis, alveolar epithelium degenerates progressively. In keeping with the goal of regenerative medicine, various models and assays to evaluate long and short term identity of stem cells and their niches is the subject of this perspective. We also report identification and characterization of functional lung stem cells to clarify how stem cell niches counteract this degenerative process. Inferences drawn from this injury model of lung degeneration using a short term assay by tracking side population cells and a long term assay tracking label retaining cells have been presented.